Construction de compromis autour d’une démarche d’accompagnement à la mise en place du plan d’aménagement de la pêcherie de la courbine en Mauritanie - Nicolas Becu; Amandine de Coninck; Moustapha Taleb Heidi; Cheikh Abdallahi Ould Inejih; Mathieu Dionnet; Jean Emmanuel Rougier; Elsa Leteurtre; Pablo N. Chavance; Moustapha Bouzouma (VertigO)
This article investigates the mechanisms which enable reaching a compromise during a companion modeling process. The study is based on the application of companion modeling during the implementation of the meager fishery development plan in Mauritania. The elaboration of fishery development plans is embedded in Mauritanian regulations and imposes consulting local stakeholders before enacting new management rules. The companion modeling process consisted in a set of workshops aiming at building a shared vision of the meager industry and its resources. State agents were involved in this process as well as professionals (wholesalers, ship owners and fishermen) and scientific experts. Several interview campaigns were undertaken to analyze the elaboration of compromises, and workshops were observed and analyzed. Based on the assumption that participatory simulation workshops are key moments, our results show that the mechanisms that favor reaching a compromise during a companion modeling process are : social learning, unveiling, modification of the way actors interact and actors’ categorization. This article also investigates the benefits of articulating the elaboration of a usual fishery development plan with a companion modeling process. The latter allows building dialog arena between all stakeholders of the fishing sector. By doing so, it ensures the quality of the deliberation process and favors the acceptance of the plan.